Development and validation of the spectrophotometric quantitative determination method of prednisolone in an ointment with hydrophilic basis - Ganeva, Elena; Proskurina, Kseniya; Ievtifieieva, Olga; Petukhova, Irina; Kizim, Olena (ScienceRise: Pharmaceutical Science, 2017)
The aim of research is to develop of the spectrophotometric quantitative determination method of prednisolone in an ointment with hydrophilic basis by a standard method and to study validation characteristics for further implementation in the laboratory for quality control of drugs. Materials and methods. The pharmacopoeial standard sample of prednisolone PSS State Pharmacopoeia of Ukraine (SPhU) No. 11/1-2143 (the content of prednisolone is 99,8 %) and hydrophilic ointment with active substance prednisolone ointment were used. The following research methods were used in the work: spectrophotometry by the standard method, methods of statistical processing of chemical experiment data. Analytical equipment, reagents, measuring glassware of class A meeting the requirements of the SPhU were used for the work. Results. The extraction method of prednisolone from an ointment with a hydrophilic base was developed: a filter ("Blue Ribbon ") was selected and the necessary extraction conditions were determined. It was found that the procedure for extracting prednisolone from the base must be repeated three times - then the concentration is 99,62 % of the nominal concentration. Optimal conditions of spectrophotometry were determined: the concentration of the analytical solution of prednisolone 2×10-5 g/ml, wavelength 244 nm. The validation characteristics of the developed method were studied: stability of the analytical solution, linearity, accuracy, convergence. Conclusions. The development of the spectrophotometric quantitative determination method of prednisolone in an ointment with a hydrophilic base by the standard method has been carried out. The assessment of validation characteristics of the method allows us to conclude that the method is acceptable for use in laboratories for quality control of drugs and can be introduced to determine prednisolone in ointments with a hydrophilic base